Utilization of several herbal plant extracts on Nile tilapia in preventing Aeromonas hydrophila and Pseudomonas sp. bacterial infection - ESTI HANDAYANI HARDI; IRAWAN WIJAYA KUSUMA; WIWIN SUWINARTI; GINA SAPTIANI; SUMOHARJO SUMOHARJO; ANGELA MARIANA LUSIASTUTI (Nusantara Bioscience, 2017)
Hardi EH, Kusuma IW, Suwinarti W, Saptiani G, Sumoharjo, Lusiastuti AM. 2017. Utilization of several herbal plant extracts on Nile Tilapia in preventing Aeromonas hydrophila and Pseudomonas sp. bacterial infection. Nusantara Bioscience 9: 220-228. This study described the effect of the ethanol extracts of temu kunci (Boesenbergia pandurata), terong asam (Solanum ferox), and lempuyang (Zingiber zerumbet) in increasing the nonspecific immunity of tilapia fish (Oreochromis niloticus) as well as in inhibiting Aeromonas hydrophila and Pseudomonas sp. infections. The ethanol extracts concentrations used in this study were: 600 and 900 ppm for B. pandurata, 400 and 900 ppm for S. ferox, and 200 and 2000 ppm for Z. zerumbet. 0.1 mL of each extract was administered via intraperitoneal injection into the tilapia fish with a weight of about 15 g. Challenge test on day 6 was done via intramuscular injection of 0.1 mL A. hydrophila and Pseudomonas bacterial suspension (density 1010 CFU/mL-1) into the fish. Thereafter, the fishes were kept for another 14 days to monitor the effectivity of the extract treatments in inhibiting pathogenic bacterial infection, by measuring several parameters such as hematocrit (He), hemoglobin (Hb), total erythrocyte (TE) on day 0 and day 14. Total leukocyte and phagocytic index were observed on day 0, 6, and 14. In addition, observations on the changes in swimming pattern, anatomic pathology, as well as fish mortality rate and relative percent survival (RPS) after challenge test were conducted as well. The results indicated that, overall, the three extracts were able to increase the total leukocyte, phagocytic index and maintain the blood parameters (He, Hb and TE) in a normal state. The protection rate against A. hydrophila observed in the fish treated with 200 and 2000 ppm Z. zerumbet extracts were 100%. Meanwhile, that of the fish supplemented with 600 and 900 ppm B. pandurata were 63% and 68%, respectively. In response to Pseudomonas sp. infection, the RPS of the fish receiving 900 ppm S. ferox was significantly higher than that treated with 400 ppm S. ferox. In conclusion, all concentrations B. pandurata, S. ferox, and Z. zerumbet extracts evaluated in this study was effective in preventing A. hydrophila and Pseudomonas sp. Infections, and had a positive impact on the nonspecific immune response which in turn enhance its capability in inhibiting pathogenic bacterial infection.